2005
DOI: 10.1099/vir.0.80766-0
|View full text |Cite
|
Sign up to set email alerts
|

A functional CD8+ cell assay reveals individual variation in CD8+ cell antiviral efficacy and explains differences in human T-lymphotropic virus type 1 proviral load

Abstract: The CD8+ lymphocyte response is a main component of host immunity, yet it is difficult to quantify its contribution to the control of persistent viruses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
92
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 80 publications
(105 citation statements)
references
References 42 publications
11
92
0
1
Order By: Relevance
“…After incubation with Tax-specific CTLs, on average 83% of Tax-expressing primary cells were lysed ( Figure 6B). In addition, the median fluorescent intensity (MFI) of Tax staining was significantly reduced after incubation with Tax-specific CTLs (Additional file 2), consistent with our previous finding that cells expressing high levels of Tax protein were preferentially killed [2,3]. In contrast, HBZ-specific CTLs did not kill a significant number of Tax-expressing cells; nor was any reduction in Tax MFI observed.…”
Section: Cd4supporting
confidence: 79%
See 1 more Smart Citation
“…After incubation with Tax-specific CTLs, on average 83% of Tax-expressing primary cells were lysed ( Figure 6B). In addition, the median fluorescent intensity (MFI) of Tax staining was significantly reduced after incubation with Tax-specific CTLs (Additional file 2), consistent with our previous finding that cells expressing high levels of Tax protein were preferentially killed [2,3]. In contrast, HBZ-specific CTLs did not kill a significant number of Tax-expressing cells; nor was any reduction in Tax MFI observed.…”
Section: Cd4supporting
confidence: 79%
“…+ cells when co-cultured directly ex vivo [1], and the rate of CTL lysis of virus-expressing cells is inversely proportional to the proviral load [2,3], a clinical predictor of disease risk.…”
Section: Htlv-1-infected Autologous Cd4mentioning
confidence: 99%
“…The same uncertainty holds for the killing rate. Asquith et al (6) estimated that CTLs specific for human T-lymphotropic virus type 1 (HTLV-1)-infected cells kill no more than five target cells per day. Stinchcombe et al (89) and Wiedemann et al (97) showed that CTLs kill the target cells that they are associated with in a few minutes.…”
Section: Resultsmentioning
confidence: 99%
“…In HTLV-1 infection, several studies have failed to show a consistent correlation between HTLV-1-specific CTL frequency and PVL levels (15). In fact, the rate of CD8 ϩ cell-mediated lysis of HTLV-1-infected cells in vitro (i.e., the efficiency of virus-specific CTLs) shows a significant negative correlation with PVL in vivo (35).…”
Section: Discussionmentioning
confidence: 99%